INVESTIGATION OF THE EIGHT GRADE STUDENTS' INTEREST IN LEARNING ENGLISH AT SMP NEGERI 4 TOTIKUM - YUSNIATI N. SABATA; VIVI KARLINA M. P. LASIBANI; SUDARTI DAHER (English Education Study Program, 2021)
Abstract The purpose of the research is to investigate the eight-grade students’ interest in learning English at SMP Negeri 4 Totikum. It was a qualitative research, and the researcher conducted interviews to collect the data. The researcher chose SMP Negeri 4 Totikum as a subject because the researcher had prior data that the students were interested in learning. Therefore, the researcher wanted to know specifically in English subject. Based on the findings of the research, the researcher concluded that majority of the eighth-grade students' interest in learning English at SMP Negeri 4 Totikum were low, majority of them uninterested in learning English. There were several factors supporting the interest, namely: attention, willingness, feeling happy, teaching materials and teachers, participation, environment, family, and society.